Dexpramipexole depletes blood and tissue eosinophils in nasal polyps with no change in polyp size. (4th October 2018) - Laidlaw, Tanya M.; Prussin, Calman; Panettieri, Reynold A.; Lee, Stella; Ferguson, Berrylin J.; Adappa, Nithin D.; Lane, Andrew P.; Palumbo, Marina L.; Sullivan, Mary; Archibald, Don; Dworetzky, Steven I.; Hebrank, Gregory T.; et al.
Abstract : Objective: Chronic rhinosinusitis with nasal polyps (CRSwNP) and eosinophilia is a disease of the upper respiratory tract for which few therapies are available. Because the oral investigational drug dexpramipexole serendipitously decreased blood eosinophils in amyotrophic lateral sclerosis studies, we assessed its safety, eosinophil‐lowering activity, and preliminary clinical efficacy in patients with CRSwNP and eosinophilia. Methods: Sixteen subjects with CRSwNP, absolute eosinophil count (AEC) ≥ 0.300 × 10 9 /L, and polyp tissue eosinophils were evaluable for efficacy in a 6‐month open‐label, multi‐center study of dexpramipexole 150 mg twice daily. The coprimary endpoints were change in AEC and change in total polyp score (TPS) from baseline to month 6, with additional clinical and histologic endpoints assessed. Results: Thirteen of 16 subjects completed 6 months of dexpramipexole treatment. Geometric mean baseline AEC was 0.525 ± 0.465 eosinophils × 10 9 /L and decreased to 0.031 ± 0.019 after 6 months of dexpramipexole treatment, a 94% reduction ( P < 0.001). Ten of 16 subjects had eosinophil counts reduced to ≤ 0.020 × 10 9 /L at month 6. In 12 subjects with nasal polyp biopsies at baseline and month 6, tissue eosinophils were reduced from a mean of 168 ± 134 to 5 ± 2 per high‐power field (HPF) ( P = 0.001), a 97% reduction from baseline. There was no significant reduction in TPS or improvement in other clinical endpoints. Dexpramipexole was well tolerated, with no drug‐related serious adverse events. Conclusion: Dexpramipexole treatment produced profound eosinophil‐lowering in peripheral blood and nasal polyp tissue. Despite the near‐elimination of polyp eosinophils, decreased TPS and nasal symptom improvement were not observed. Level of Evidence: 2 Laryngoscope, 129:E61–E66, 2019